“Like Puah and Shiphrah”: Jewish Midwives in Eighteenth-Century Germany - Zinger, Nimrod (The Jewish quarterly review, 2022)
Using the memorbikher literature, which has received only little scholarly attention so far, this article explores the position of the Jewish midwife in eighteenth-century Germany. The memorbikher genre allows us to decipher the activity of many Jewish women who were involved in midwifery and did not leave any trace in other sources from the period. It shows that boundaries between “official” and “unofficial,” “professional” and “unprofessional” midwives were fuzzy, and that a significant number of deliveries in the Jewish community were performed by midwives who were not connected to any formal authority., The article also traces the case of Haya’le, the Offenbach community’s official midwife, who was active in the city in the mid-eighteenth century, and whose illuminating case is described in detail in the local pinkas. Haya’le’s case enables us to grasp the complex status of Jewish midwives and to see them as active players who had the power to improve their positions, not as passive victims of the male establishment. The examination of memorbikher and pinkasim together provides a more complete picture of Jewish midwives in this period, and points to shifts in their social position that constituted an institutionalization of Jewish midwifery.